2011
DOI: 10.1007/s00330-011-2248-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of postmortem multidetector computed tomography in the detection of fatal findings related to cause of non-traumatic death in the emergency department

Abstract: PMMDCT is a feasible tool for detecting morphological fatal findings in non-traumatic death in ED. It is important to know the ability and limitation of PMMDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Postmortem magnetic resonance (PMMR) imaging has shown that MR signals and image contrast change after death. 8 -10 Optimization of parameters for PMMR imaging and accurate interpretation of imaging findings require analyses of quantified data.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Postmortem magnetic resonance (PMMR) imaging has shown that MR signals and image contrast change after death. 8 -10 Optimization of parameters for PMMR imaging and accurate interpretation of imaging findings require analyses of quantified data.…”
Section: Introductionmentioning
confidence: 99%
“…However, in countries with a low autopsy rate, such as Japan, many causes of death are diagnosed by ante-mortem clinical presentation and post-mortem examinations without PMCT or autopsy [4,8]. Comparison of ante-mortem clinical presentation and postmortem examinations with PMCT results is useful for determining whether PMCT examinations are necessary in such countries.…”
Section: Discussionmentioning
confidence: 97%
“…In Japan and other nations that have low autopsy rates, PMCT is used more widely to diagnose causes of death, as discussed in several previous articles [1,[10][11][12]. These studies, however, have generally had low numbers of cadavers or have been limited to natural deaths.…”
Section: Introductionmentioning
confidence: 96%